Pengaruh Laba Bersih Dan Arus Kas Operasi Terhadap Financial Distress - Nur Tiyas Abdul Rahim; Sahmin Noholo; Siti Pratiwi Husain (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
The purpose of this study is to obtain empirical evidence on the effect of net profit dan operating cash flow on financial distress in cosmetics dan household use sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017 to 2021 period. This study used purposive sampling method to select dan select 5 companies dan 25 data from cosmetics dan household use sub-sector companies. The data in this study was collected dan processed using Microsoft Excel 2019 dan SPSS 26. The results of this study show that net profit dan operating cash flow do not have a significant effect on financial distress, but simultaneously affect financial distress.